2020
DOI: 10.3389/fpsyt.2020.00012
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Sensory Processing During Low-Oxygen Exposure: A Noninvasive Approach to Detecting Changes in Cognitive States

Abstract: The ability to detect novelty in our environment is a critical sensory function. A reliable set of event-related potentials (ERP), known as the auditory deviance response (ADR), are elicited in the absence of directed attention and indexes functionally relevant networks. The ADR consists of three peaks: mismatch negativity (MMN), P3a, and reorienting negativity (RON) that are sequentially evoked in response to unattended changes in repetitive background stimulation. While previous studies have established the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 43 publications
2
21
0
Order By: Relevance
“…A passive auditory oddball paradigm was used to elicit MMN and P3a. Consistent with Seech et al [ 21 ], 85% of the tones were standards (50 ms, 1000 Hz, n = 2754) and 15% were deviants (7.5%, n = 243 per deviant type) that differed in stimulus duration (100 ms, 1000 Hz) or both duration and frequency (i.e., “double deviant” 100 ms, 1100 Hz). All tones had 5-ms rise/fall times and were presented with a fixed 500-ms stimulus onset asynchrony.…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…A passive auditory oddball paradigm was used to elicit MMN and P3a. Consistent with Seech et al [ 21 ], 85% of the tones were standards (50 ms, 1000 Hz, n = 2754) and 15% were deviants (7.5%, n = 243 per deviant type) that differed in stimulus duration (100 ms, 1000 Hz) or both duration and frequency (i.e., “double deviant” 100 ms, 1100 Hz). All tones had 5-ms rise/fall times and were presented with a fixed 500-ms stimulus onset asynchrony.…”
Section: Methodssupporting
confidence: 84%
“…Results of the present study support the continued use of highdensity EEG recording of ASSR, MMN, and P3a as pharmacodynamic endpoints in clinical trials. These measures were selected based on several criteria described in the literature [25][26][27][28], including ease of rapid assessment with high-density montages [19,20] for characterization of neural substrates, substantial test-retest reliability [29], relationships to cognition and daily functioning [17,20,[30][31][32][33][34][35], and sensitivity to pharmacologic [19,22] and non-pharmacologic interventions [36][37][38][39]/perturbations [21]. The primary limitation of this study is the small patient population because of which it is underpowered for detection of treatment-induced effects for the key physiological biomarkers or cognitive assessments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MMN/P3a complex is a reliable neural index of automatic and preattentive stages of information processing. Previous work has demonstrated that these ERPs are disrupted both within the auditory ( Seech et al, 2020 ; Blacker and McHail, 2021 ) and visual ( Blacker et al, 2021 ) domains. Broadly speaking, ERPs are often classified as “cognitive” or “sensory” ERPs.…”
Section: Introductionmentioning
confidence: 97%
“…Previous work has demonstrated that hypoxic exposure disrupts the mismatch negativity (MMN) and P3a event-related potentials (ERP; Seech et al, 2020 ; Blacker and McHail, 2021 ; Blacker et al, 2021 ). The MMN/P3a complex is a reliable neural index of automatic and preattentive stages of information processing.…”
Section: Introductionmentioning
confidence: 99%